Reassessing the Impact of Option Introductions on Market Quality: A Less Restrictive Test for Event-Date Effects - Danielsen, Bartley R.; van Ness, Bonnie F.; Warr, Richard S. (Journal of Financial and Quantitative Analysis, 2007)
Abstract Prior research concludes that option introductions improve the average liquidity of the underlying stocks. We develop an improved, generalizable test to assess whether market quality changes occur on or near an event date. Applying this method to option listing events, we conclude that options do not systematically improve the market quality of the underlying security; rather, the market quality of the underlying security improves before the listing decision. Hazard model tests indicate that improving liquidity is a selection criterion in the option listing decision. Moreover, these tests suggest that the size of a stock's bid-ask spread is the single most important option listing determinant.